Psychological Hardiness and its Relation to Social Networking Sites Addiction among a Sample of Female Adolescents in Jeddah - Mansoor, Sara Naif; Hamididdin, Radeah Mohammed (Journal of Educational and Psychological Sciences, 2023)
The current study aimed at recognizing the relationship between psychological hardiness and social networking sites addiction among a sample of female adolescents in Jeddah, and recognizing their level of psychological hardiness and social networking sites addiction, and exploring the differences in level of psychological hardiness and social networking sites addiction among the study sample individuals, according to (academic average) variable. The study adopted the descriptive approach with its two correlational and comparative aspects. The sample of study consisted of (434) female students from both the preparatory and secondary stages. The researcher used the Psychological Hardiness Scale and the Social Networking Sites Addiction Scale as tools of study. The results indicated the existence of a negative correlation between psychological hardiness and social networking sites addiction, as well as the existence of a high level of psychological hardiness among the study sample individuals, where the "commitment" dimension was the highest level among sample individuals. In contrast, there was a moderate level of social networking sites addiction, as the highest level was the "mood change" dimension. Moreover, the study concluded that there were no statistically significant differences in psychological hardiness according to the (academic average) variable, in addition to the existence of statistically significant differences in social networking sites addiction, according to the (academic average) variable. Based on the results of the study, the researcher recommended attempting to launch awareness campaigns for female adolescents that aim to encourage them to responsible use of social networking sites and preparing educational programs directed to parents, concentrating on the importance of developing psychological hardiness of sons and daughters since early age.
Keywords: Psychological hardiness; social networking sites addiction; female adolescents; Tik Tok; Snapchat